Jordan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses the Syrian Refugee Crisis (SRC) and conflicts in Syria and Iraq have weighed on investor sentiment, tourism, and exports but the influx of Syrians is likely to have increased aggregate demand. Labor market conditions deteriorated after the massive influx of refugees and nontradable prices accelerated. The balance of payment suffered pressures on the non-oil current account, owing to lower exports of goods and services and higher imports. The SRC has increased the direct fiscal costs persistently by above one percent of GDP, which could double after counting for quality and capital deterioration. The negative impact is decreasing as the influx of Syrian refugees slowed and the stock pushed up aggregate demand. The influx of more than 10 percent of Jordan's original population may have certainly increased consumption, particularly, over time as the incomers settled and the likelihood of returning to their home country diminishes. Unemployment grew the most in governorates that host most of the refugees.